2014
DOI: 10.1186/1471-2288-14-70
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of publication bias in meta-analyses of diagnostic test accuracy: a meta-epidemiological study

Abstract: BackgroundThe validity of a meta-analysis can be understood better in light of the possible impact of publication bias. The majority of the methods to investigate publication bias in terms of small study-effects are developed for meta-analyses of intervention studies, leaving authors of diagnostic test accuracy (DTA) systematic reviews with limited guidance. The aim of this study was to evaluate if and how publication bias was assessed in meta-analyses of DTA, and to compare the results of various statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
213
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(215 citation statements)
references
References 72 publications
(33 reference statements)
1
213
1
Order By: Relevance
“…Hierarchical summary receiver operating characteristic (HSROC) curves with both 95% CIs and 95% prediction contours were also created. Publication bias was tested using Deeks test 39,40 with an a priori significance of P < .10.…”
Section: Resultsmentioning
confidence: 99%
“…Hierarchical summary receiver operating characteristic (HSROC) curves with both 95% CIs and 95% prediction contours were also created. Publication bias was tested using Deeks test 39,40 with an a priori significance of P < .10.…”
Section: Resultsmentioning
confidence: 99%
“…There are many terms used to describe biases related to the selective dissemination of evidence, such as language bias, funding bias, database bias, citation bias, location bias, reviewer bias (Bax and Moons, 2011) and outcome reporting bias (selective reporting of positive outcomes). These forms of biases tend to have more effect on small studies and contribute to the phenomenon of "small study-effects" (van Enst et al, 2014). This means that published studies with small sample sizes tend to have larger and more favourable effects compared to studies with larger sample sizes.…”
Section: Practical Obstacles In Meta-analysismentioning
confidence: 99%
“…In the absence of bias, the plot sould resemble a 'funnel shape', in the presence of publication bias, some smaller studies reporting negative results will be missing and an asymmetrical funnel plot will be observed thus publication bias is not the only possible reason for observed funnel plot asymmetry (Peters et al, 2006). Egger's and Begg's regression tests are commonly used statistical tests for publication bias (van Enst et al, 2014).…”
Section: Practical Obstacles In Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, van Enst et al had found that most systematic reviews of diagnostic test mentioned the issue, but only with 41% measuring PB [4]. Ioannidis and Trikalinos explored PB problem in 1,669 Cochrane reviews, ultimately analyzed 6,873 meta-analyses, and they found a half of the metaanalyses had no statistically significant results.…”
Section: Introductionmentioning
confidence: 99%